2022
DOI: 10.1371/journal.pone.0262956
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile, antimicrobial susceptibility patterns, and associated factors of community-acquired pneumonia among adult patients in Gondar, Northwest Ethiopia: A cross-sectional study

Abstract: Introduction Community-acquired pneumonia is associated with higher morbidity, hospitalization, and mortality in adults. Likewise, antimicrobial resistance has increased in recent decades in Ethiopia. Therefore, this study was aimed to determine the bacterial isolates, their antimicrobial susceptibility patterns, and factors associated with community-acquired pneumonia among adult patients in Gondar, Northwest Ethiopia. Materials and methods This institutional-based cross-sectional study was conducted from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 56 publications
(94 reference statements)
1
21
1
1
Order By: Relevance
“…The phenotypic analysis of the inducible resistance in S. aureus to clindamycin was demonstrated through the D -test across African countries. In this review study, the prevalence of inducible clindamycin resistance among the S. aureus isolates was found to be 19.8%, ranging from 2.9 to 44.0% [ 12 33 ]. Various studies have reported a comparable proportion of inducible clindamycin resistance among S. aureus isolates obtained from human sources such as studies in Odisha state, eastern India, 22.0% [ 7 ]; Nepal, 23.4% [ 34 ]; Malaysia, 22.1% [ 35 ]; and Israel, 20.0% to 25.0% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotypic analysis of the inducible resistance in S. aureus to clindamycin was demonstrated through the D -test across African countries. In this review study, the prevalence of inducible clindamycin resistance among the S. aureus isolates was found to be 19.8%, ranging from 2.9 to 44.0% [ 12 33 ]. Various studies have reported a comparable proportion of inducible clindamycin resistance among S. aureus isolates obtained from human sources such as studies in Odisha state, eastern India, 22.0% [ 7 ]; Nepal, 23.4% [ 34 ]; Malaysia, 22.1% [ 35 ]; and Israel, 20.0% to 25.0% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the overall prevalence of the iMLSB phenotype in MRSA was calculated by adding all the number of iMLSB phenotypes and dividing it by the total number of MRSA isolates, which was 26.8% (279/1041). Studies were conducted between 2007 and 2021 from different areas of the country [ 12 33 ].…”
Section: The Geographic Area Of Studies Reported Inducible Clindamyci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonia is one of the leading causes of death among Ethiopian children under the age of five, accounting for 28% of all deaths [ 33 ]. Previous reports in Africa showed GNB prevalence in CAP with 49.7% to 56.7% in Ethiopia [ 4 , 37 , 38 ], 83.1% in Tanzania [ 39 ], and 76.2% in Sudan [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were tested for saliva, mucus, blood, and mucoid material 10 . Sample Processing: Electrolytes were performed on Alinity 11 , Sputum culture was performed by inoculating sputum on blood, chocolate and MacConkey agar 12 . AFB was tested by GeneXpert 13 .…”
Section: Introductionmentioning
confidence: 99%